2007
DOI: 10.1111/j.1365-2753.2006.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Delivering feedback on learning organization characteristics – using a Learning Practice Inventory

Abstract: Our study suggests that a robust feedback process on collective capacity for learning and change can be identified that is useful and feasible. A key implication is that some form of educational support is required, and this work will take place as part of an ongoing programme of research by the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Sometimes problems of practice emerge that require active problem solving. This type of problem solving has the potential to alter and inform future practice (Regehr & Mylopoulos, 2008), That is, to innovate, Myopolous & Scardamalia (2008) take this a step further to account for the collective learning that occurs through "collaborative iterative idea improvement" (p, 976), a process whereby practices evolve and develop through sharing of different perspectives, (2) Learning for practice improvement Within health, learning is at the core of the quality improvement process (Kelly et al,, 2007), Under-pinned by educational principles of experiential learning and reflective practice, quality improvement provides a structured means by which innovations in system processes can be realized (Wilson & Harrison, 2002), Built into this process are three key questions: (1) What are we trying to accomplish? (2) What changes can we make?…”
Section: A Focus On Learning Rather Than Workingmentioning
confidence: 98%
“…Sometimes problems of practice emerge that require active problem solving. This type of problem solving has the potential to alter and inform future practice (Regehr & Mylopoulos, 2008), That is, to innovate, Myopolous & Scardamalia (2008) take this a step further to account for the collective learning that occurs through "collaborative iterative idea improvement" (p, 976), a process whereby practices evolve and develop through sharing of different perspectives, (2) Learning for practice improvement Within health, learning is at the core of the quality improvement process (Kelly et al,, 2007), Under-pinned by educational principles of experiential learning and reflective practice, quality improvement provides a structured means by which innovations in system processes can be realized (Wilson & Harrison, 2002), Built into this process are three key questions: (1) What are we trying to accomplish? (2) What changes can we make?…”
Section: A Focus On Learning Rather Than Workingmentioning
confidence: 98%
“…A recent study of military personnel found that feedback of data and revelation of problematic areas or deficits was more likely to result in the survey being perceived as useful and, in turn, influenced respondents’ intentions to complete future surveys [14]. In a 2007 study of processes and formats for feedback of survey results to healthcare practices, researchers identified a useful and feasible feedback mechanism, which involved a feedback session comprising visual presentation of aggregated data in the form of dot plots [15]. …”
Section: Introductionmentioning
confidence: 99%
“…By ‘collective learning’ we refer to learning held in common ‘by a group who share a common health goal and common objectives, determined by community needs, to the achievement of which each member of the team contributes, in accordance with his or her competence and skill and in co‐ordination with the functions of others’ (World Health Organization definition of a health care team) 5 . This study was undertaken to inform the development of the ‘Learning Practice’ initiative, 6–10 which encourages ‘learning organisation’ characteristics through a facilitated learning programme with primary care teams.…”
Section: Introductionmentioning
confidence: 99%